Mobile-assisted Language Learning and Advanced-level Second Language Acquisition - Burston, Jack; Athanasiou, Androulla (My University, 2025)
The focus of this monograph is on the contribution of Mobile-Assisted Language Learning (MALL) to ubiquitous access for advanced-level second language (AL2) learning. Its intended audience is second language teacher trainers, practicing foreign language teachers, and foreign language program administrators as well as researchers in the field of AL2 acquisition in general and CALL and MALL in particular. In accordance with the proficiency descriptors of both the American Council on the Teaching of Foreign Languages (ACTFL) and the Common European Framework of Reference for Languages (CEFR), AL2 learners need most of all to work on discourse-pragmatic competence and actively increase their intercultural/sociolinguistic awareness. This can only be achieved through interpersonal interactions, preferably in real-time. And this is where MALL can make the greatest contribution to ubiquitously accessible AL2 learning. In describing the contribution of MALL to AL2, this monograph firstly endeavors to provide a comprehensive account of the role that Mobile-Assisted Language Learning (MALL) has played in the teaching and learning of advanced-level second/foreign languages (AL2) over the past three decades, as reflected in published experimental research. Secondly, it investigates the current state of AL2 MALL curricular integration. Lastly, it considers the role of MALL within the institutional context of the professional development of advanced-level foreign language teachers and seeks to determine the influence of MALL upon the restructuring of AL2 programs, those targeting languages for specific purposes as well as those for L2 majors.
Keywords: mobile-assisted language learning; advanced-level second language acquisition; teacher training